2014
DOI: 10.1002/cctc.201402525
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Requirements for Palladium–Aluminium Triflate Co‐catalysed Hydromethoxycarbonylation Reactions of Alkynes Bearing Oxygen Atoms

Abstract: The palladium diacetate–aluminium triflate combination is an effective catalyst for the hydromethoxycarbonylation reaction of isolated alkenes and alkynes. However, its application in the hydromethoxycarbonylation of oxygen atom‐bearing alkynes is non‐trivial: the position relative to the alkyne (e.g., allylic, homoallylic) and nature of the oxygen atom determine the success of the transformation. We detail the minimum structural requirements for a successful outcome with ether‐containing alkyne substrates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Initially, Al(OTf) 3 was used at high catalyst loading and at low temperature, producing high M W products with little color and of relatively high T g in a fast reaction (Table 4, entry 1). 37 Catalyst loading could be reduced 40-fold which is a remarkably low acid catalyst level for this transformation; compared to a sulfuric acid catalyzed reaction this is particularly time-efficient (Table 4, entries 2−4). The lower catalyst levels required longer reaction times and produced lower M W cellulose ester products but with the desirable (for our application) characteristic of depressed T g values.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, Al(OTf) 3 was used at high catalyst loading and at low temperature, producing high M W products with little color and of relatively high T g in a fast reaction (Table 4, entry 1). 37 Catalyst loading could be reduced 40-fold which is a remarkably low acid catalyst level for this transformation; compared to a sulfuric acid catalyzed reaction this is particularly time-efficient (Table 4, entries 2−4). The lower catalyst levels required longer reaction times and produced lower M W cellulose ester products but with the desirable (for our application) characteristic of depressed T g values.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is likely that the catalyst was behaving as a Lewis acid−assisted Brønsted acid, a feature of Al(OTf) 3 we have investigated and discussed over a period of time. 37,38 The unexpectedly high activity of Al(OTf) 3 in this reaction gives product with low color and the catalyst is recyclable, 39 thereby improving the environmental impact of the process. While Yb(OTf) 3 afforded some activity as an esterification catalyst, though much less so than Al(OTf) 3 , Gd(OTf) 3 failed altogether to catalyze the esterification of cellulose to produce BLAC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite belonging to the same group III metals of the periodic table, some differences between the two salts are expected, owing to their intrinsic characteristics (covalent and ionic radii, polarizability, electronegativity, d‐orbitals…). On the other hand, many reactions developed with metal triflates involve the activation of a carbonyl group by complexation,,,,,,,,, or by chelation of 1,n‐carbonyl derivatives ,,. Among the carbonyl‐based chemical functions, amides are relatively strong Lewis bases and have been used in a wide array of synthetic applications .…”
Section: Introductionmentioning
confidence: 99%
“…More recently Williams reinvestigated the reaction [19] and suggested that the low reactivity and selectivity obtained are likely due to chelation of the triple bond and the oxygen atom of the propargyl alcohol to the catalyst metal centre.…”
Section: Introductionmentioning
confidence: 99%